Question
upstudy study bank question image url

36 Résoudre dans \( \mathbb{R} \times \mathbb{R} \) les systèmes d'équations suivants : (1) \( \left\{\begin{aligned} x+y & =-1 \\ x y & =-1\end{aligned}\right. \) (4) \( \left\{\begin{aligned} \frac{x^{2}}{y}+\frac{y^{2}}{x} & =0 \\ x y & =-1\end{aligned}\right. \) (2) \( \left\{\begin{aligned} x^{2}+y^{2} & =5 \\ x y & =-2\end{aligned}\right. \) (5) \( \left\{\begin{aligned} x^{4}+y^{4} & =17 \\ x y & =2\end{aligned}\right. \) (3) \( \left\{\begin{array}{l}x^{2}+y^{2}=20 \\ \frac{x}{y}+\frac{y}{x}=\frac{5}{2}\end{array}\right. \) (6) \( \left\{\begin{aligned} x-y & =2 \\ x y & =35\end{aligned}\right. \) 37 Résoudre dans \( \mathbb{R} \) les équations suivantes : (1) \( 2 x|x|-6 x-2=0 \); (2) \( 2 x^{2}-3 x+5=|x-1| \) 38 On considère l'équation :

Ask by Garrett Nunez. in Gabon
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Voici les solutions simplifiées pour les systèmes d'équations et les équations demandées : ### Systèmes d'équations 1. \( x + y = -1 \) et \( x y = -1 \): - Solutions: \( (x, y) = (-1, 1) \) et \( (1, -1) \) 2. \( \frac{x^2}{y} + \frac{y^2}{x} = 0 \) et \( x y = -1 \): - Solutions: \( (x, y) = (-1, 1) \) et \( (1, -1) \) 3. \( x^2 + y^2 = 5 \) et \( x y = -2 \): - Solutions: \( (x, y) = (-1, 2) \), \( (-2, 1) \), \( (1, -2) \), \( (2, -1) \) 4. \( x^4 + y^4 = 17 \) et \( x y = 2 \): - Solutions: \( (x, y) = (-1, -2) \), \( (-2, -1) \), \( (1, 2) \), \( (2, 1) \) 5. \( x^2 + y^2 = 20 \) et \( \frac{x}{y} + \frac{y}{x} = \frac{5}{2} \): - Solutions: \( (x, y) = (-2, -4) \), \( (-4, -2) \), \( (2, 4) \), \( (4, 2) \) 6. \( x - y = 2 \) et \( x y = 35 \): - Solutions: \( (x, y) = (-5, -7) \) et \( (7, 5) \) ### Équations 1. \( 2 x|x| - 6 x - 2 = 0 \): - Solutions: \( x = -\frac{3 + \sqrt{5}}{2} \), \( x = \frac{-3 + \sqrt{5}}{2} \), \( x = \frac{3 + \sqrt{13}}{2} \) 2. \( 2 x^2 - 3 x + 5 = |x - 1| \): - Aucune solution réelle Si vous avez besoin de plus d'informations ou d'autres questions, n'hésitez pas à demander !

Solution

Solve the equation by following steps: - step0: Solve for \(x\): \(2x^{2}-3x+5=\left|x-1\right|\) - step1: Move the expression to the left side: \(2x^{2}-3x+5-\left|x-1\right|=0\) - step2: Separate into possible cases: \(\begin{align}&2x^{2}-3x+5-\left(x-1\right)=0,x-1\geq 0\\&2x^{2}-3x+5-\left(-\left(x-1\right)\right)=0,x-1<0\end{align}\) - step3: Solve the equation: \(\begin{align}&x \notin \mathbb{R},x\geq 1\\&x \notin \mathbb{R},x<1\end{align}\) - step4: Find the intersection: \(\begin{align}&x \notin \mathbb{R}\\&x \notin \mathbb{R}\end{align}\) - step5: Find the union: \(x \notin \mathbb{R}\) Solve the system of equations \( x^{4}+y^{4}=17;xy=2 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x^{4}+y^{4}=17\\xy=2\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x^{4}+y^{4}=17\\x=\frac{2}{y}\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(\frac{2}{y}\right)^{4}+y^{4}=17\) - step3: Simplify: \(\frac{16+y^{8}}{y^{4}}=17\) - step4: Cross multiply: \(16+y^{8}=y^{4}\times 17\) - step5: Simplify the equation: \(16+y^{8}=17y^{4}\) - step6: Move the expression to the left side: \(16+y^{8}-17y^{4}=0\) - step7: Factor the expression: \(\left(2-y\right)\left(1-y\right)\left(1+y\right)\left(2+y\right)\left(1+y^{2}\right)\left(4+y^{2}\right)=0\) - step8: Separate into possible cases: \(2-y=0\cup 1-y=0\cup 1+y=0\cup 2+y=0\cup 1+y^{2}=0\cup 4+y^{2}=0\) - step9: Solve the equation: \(y=2\cup y=1\cup y=-1\cup y=-2\cup y \notin \mathbb{R}\cup y \notin \mathbb{R}\) - step10: Find the union: \(y=2\cup y=1\cup y=-1\cup y=-2\) - step11: Rearrange the terms: \(\left\{ \begin{array}{l}x=\frac{2}{y}\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2}{y}\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2}{y}\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2}{y}\\y=-2\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=1\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=-1\\y=-2\end{array}\right.\) - step13: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=1\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=-1\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=1\end{array}\right.\) - step15: Rewrite: \(\left(x,y\right) = \left(-1,-2\right)\cup \left(x,y\right) = \left(-2,-1\right)\cup \left(x,y\right) = \left(1,2\right)\cup \left(x,y\right) = \left(2,1\right)\) Solve the system of equations \( x-y=2;xy=35 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x-y=2\\xy=35\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=2+y\\xy=35\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(2+y\right)y=35\) - step3: Simplify: \(y\left(2+y\right)=35\) - step4: Expand the expression: \(2y+y^{2}=35\) - step5: Move the expression to the left side: \(2y+y^{2}-35=0\) - step6: Factor the expression: \(\left(y-5\right)\left(y+7\right)=0\) - step7: Separate into possible cases: \(\begin{align}&y-5=0\\&y+7=0\end{align}\) - step8: Solve the equation: \(\begin{align}&y=5\\&y=-7\end{align}\) - step9: Calculate: \(y=5\cup y=-7\) - step10: Rearrange the terms: \(\left\{ \begin{array}{l}x=2+y\\y=5\end{array}\right.\cup \left\{ \begin{array}{l}x=2+y\\y=-7\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=7\\y=5\end{array}\right.\cup \left\{ \begin{array}{l}x=-5\\y=-7\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-5\\y=-7\end{array}\right.\cup \left\{ \begin{array}{l}x=7\\y=5\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-5\\y=-7\end{array}\right.\cup \left\{ \begin{array}{l}x=7\\y=5\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-5,-7\right)\cup \left(x,y\right) = \left(7,5\right)\) Solve the equation \( 2x|x|-6x-2=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(2x\left|x\right|-6x-2=0\) - step1: Separate into possible cases: \(\begin{align}&2x\times x-6x-2=0,x\geq 0\\&2x\left(-x\right)-6x-2=0,x<0\end{align}\) - step2: Solve the equation: \(\begin{align}&\begin{align}&x=\frac{3+\sqrt{13}}{2}\\&x=\frac{3-\sqrt{13}}{2}\end{align},x\geq 0\\&\begin{align}&x=\frac{-3+\sqrt{5}}{2}\\&x=-\frac{3+\sqrt{5}}{2}\end{align},x<0\end{align}\) - step3: Find the intersection: \(\begin{align}&x=\frac{3+\sqrt{13}}{2}\\&x=\frac{-3+\sqrt{5}}{2}\\&x=-\frac{3+\sqrt{5}}{2}\end{align}\) - step4: Rewrite: \(x_{1}=-\frac{3+\sqrt{5}}{2},x_{2}=\frac{-3+\sqrt{5}}{2},x_{3}=\frac{3+\sqrt{13}}{2}\) Solve the system of equations \( x^{2}+y^{2}=20;\frac{x}{y}+\frac{y}{x}=\frac{5}{2} \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x^{2}+y^{2}=20\\\frac{x}{y}+\frac{y}{x}=\frac{5}{2}\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x^{2}+y^{2}=20\\x=\frac{y}{2}\cup x=2y\end{array}\right.\) - step2: Evaluate: \(\left\{ \begin{array}{l}x^{2}+y^{2}=20\\x=\frac{y}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x^{2}+y^{2}=20\\x=2y\end{array}\right.\) - step3: Calculate: \(\left\{ \begin{array}{l}x=-2\\y=-4\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=4\end{array}\right.\cup \left\{ \begin{array}{l}x=-4\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=4\\y=2\end{array}\right.\) - step4: Rearrange the terms: \(\left\{ \begin{array}{l}x=-2\\y=-4\end{array}\right.\cup \left\{ \begin{array}{l}x=-4\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=4\end{array}\right.\cup \left\{ \begin{array}{l}x=4\\y=2\end{array}\right.\) - step5: Check the solution: \(\left\{ \begin{array}{l}x=-2\\y=-4\end{array}\right.\cup \left\{ \begin{array}{l}x=-4\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=4\end{array}\right.\cup \left\{ \begin{array}{l}x=4\\y=2\end{array}\right.\) - step6: Rewrite: \(\left(x,y\right) = \left(-2,-4\right)\cup \left(x,y\right) = \left(-4,-2\right)\cup \left(x,y\right) = \left(2,4\right)\cup \left(x,y\right) = \left(4,2\right)\) Solve the system of equations \( \frac{x^{2}}{y}+\frac{y^{2}}{x}=0;xy=-1 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}\frac{x^{2}}{y}+\frac{y^{2}}{x}=0\\xy=-1\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}\frac{x^{2}}{y}+\frac{y^{2}}{x}=0\\x=-\frac{1}{y}\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\frac{\left(-\frac{1}{y}\right)^{2}}{y}+\frac{y^{2}}{-\frac{1}{y}}=0\) - step3: Simplify: \(\frac{1}{y^{3}}-y^{3}=0\) - step4: Multiply both sides of the equation by LCD: \(\left(\frac{1}{y^{3}}-y^{3}\right)y^{3}=0\times y^{3}\) - step5: Simplify the equation: \(1-y^{6}=0\) - step6: Rewrite the expression: \(-y^{6}=-1\) - step7: Change the signs: \(y^{6}=1\) - step8: Simplify the expression: \(y=\pm \sqrt[6]{1}\) - step9: Simplify: \(y=\pm 1\) - step10: Separate into possible cases: \(y=1\cup y=-1\) - step11: Rearrange the terms: \(\left\{ \begin{array}{l}x=-\frac{1}{y}\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{1}{y}\\y=-1\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-1\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-1\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-1\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-1,1\right)\cup \left(x,y\right) = \left(1,-1\right)\) Solve the system of equations \( x+y=-1;xy=-1 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x+y=-1\\xy=-1\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-1-y\\xy=-1\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(-1-y\right)y=-1\) - step3: Simplify: \(y\left(-1-y\right)=-1\) - step4: Expand the expression: \(-y-y^{2}=-1\) - step5: Move the expression to the left side: \(-y-y^{2}-\left(-1\right)=0\) - step6: Remove the parentheses: \(-y-y^{2}+1=0\) - step7: Rewrite in standard form: \(-y^{2}-y+1=0\) - step8: Multiply both sides: \(y^{2}+y-1=0\) - step9: Solve using the quadratic formula: \(y=\frac{-1\pm \sqrt{1^{2}-4\left(-1\right)}}{2}\) - step10: Simplify the expression: \(y=\frac{-1\pm \sqrt{5}}{2}\) - step11: Separate into possible cases: \(\begin{align}&y=\frac{-1+\sqrt{5}}{2}\\&y=\frac{-1-\sqrt{5}}{2}\end{align}\) - step12: Rewrite the fraction: \(\begin{align}&y=\frac{-1+\sqrt{5}}{2}\\&y=-\frac{1+\sqrt{5}}{2}\end{align}\) - step13: Evaluate the logic: \(y=\frac{-1+\sqrt{5}}{2}\cup y=-\frac{1+\sqrt{5}}{2}\) - step14: Rearrange the terms: \(\left\{ \begin{array}{l}x=-1-y\\y=\frac{-1+\sqrt{5}}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x=-1-y\\y=-\frac{1+\sqrt{5}}{2}\end{array}\right.\) - step15: Calculate: \(\left\{ \begin{array}{l}x=-\frac{1+\sqrt{5}}{2}\\y=\frac{-1+\sqrt{5}}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{-1+\sqrt{5}}{2}\\y=-\frac{1+\sqrt{5}}{2}\end{array}\right.\) - step16: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{1+\sqrt{5}}{2}\\y=\frac{-1+\sqrt{5}}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{-1+\sqrt{5}}{2}\\y=-\frac{1+\sqrt{5}}{2}\end{array}\right.\) - step17: Rewrite: \(\left(x,y\right) = \left(-\frac{1+\sqrt{5}}{2},\frac{-1+\sqrt{5}}{2}\right)\cup \left(x,y\right) = \left(\frac{-1+\sqrt{5}}{2},-\frac{1+\sqrt{5}}{2}\right)\) Solve the system of equations \( x^{2}+y^{2}=5;xy=-2 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x^{2}+y^{2}=5\\xy=-2\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x^{2}+y^{2}=5\\x=-\frac{2}{y}\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(-\frac{2}{y}\right)^{2}+y^{2}=5\) - step3: Simplify: \(\frac{4+y^{4}}{y^{2}}=5\) - step4: Cross multiply: \(4+y^{4}=y^{2}\times 5\) - step5: Simplify the equation: \(4+y^{4}=5y^{2}\) - step6: Move the expression to the left side: \(4+y^{4}-5y^{2}=0\) - step7: Factor the expression: \(\left(2-y\right)\left(1-y\right)\left(1+y\right)\left(2+y\right)=0\) - step8: Separate into possible cases: \(2-y=0\cup 1-y=0\cup 1+y=0\cup 2+y=0\) - step9: Solve the equation: \(y=2\cup y=1\cup y=-1\cup y=-2\) - step10: Rearrange the terms: \(\left\{ \begin{array}{l}x=-\frac{2}{y}\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{2}{y}\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{2}{y}\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{2}{y}\\y=-2\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=-1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-2\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=-1\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-1\\y=2\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=-1\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-1,2\right)\cup \left(x,y\right) = \left(-2,1\right)\cup \left(x,y\right) = \left(1,-2\right)\cup \left(x,y\right) = \left(2,-1\right)\) Voici les solutions pour les systèmes d'équations et les équations demandées : ### Systèmes d'équations 1. Pour le système \( \left\{\begin{aligned} x+y & =-1 \\ x y & =-1\end{aligned}\right. \): - Solutions : \[ (x,y) = \left(-\frac{1+\sqrt{5}}{2}, \frac{-1+\sqrt{5}}{2}\right) \cup (x,y) = \left(\frac{-1+\sqrt{5}}{2}, -\frac{1+\sqrt{5}}{2}\right) \] 2. Pour le système \( \left\{\begin{aligned} \frac{x^{2}}{y}+\frac{y^{2}}{x} & =0 \\ x y & =-1\end{aligned}\right. \): - Solutions : \[ (x,y) = (-1,1) \cup (x,y) = (1,-1) \] 3. Pour le système \( \left\{\begin{aligned} x^{2}+y^{2} & =5 \\ x y & =-2\end{aligned}\right. \): - Solutions : \[ (x,y) = (-1,2) \cup (x,y) = (-2,1) \cup (x,y) = (1,-2) \cup (x,y) = (2,-1) \] 4. Pour le système \( \left\{\begin{aligned} x^{4}+y^{4} & =17 \\ x y & =2\end{aligned}\right. \): - Solutions : \[ (x,y) = (-1,-2) \cup (x,y) = (-2,-1) \cup (x,y) = (1,2) \cup (x,y) = (2,1) \] 5. Pour le système \( \left\{\begin{aligned} x^{2}+y^{2} & =20 \\ \frac{x}{y}+\frac{y}{x}=\frac{5}{2}\end{aligned}\right. \): - Solutions : \[ (x,y) = (-2,-4) \cup (x,y) = (-4,-2) \cup (x,y) = (2,4) \cup (x,y) = (4,2) \] 6. Pour le système \( \left\{\begin{aligned} x-y & =2 \\ x y & =35\end{aligned}\right. \): - Solutions : \[ (x,y) = (-5,-7) \cup (x,y) = (7,5) \] ### Équations 1. Pour l'équation \( 2 x|x|-6 x-2=0 \): - Solutions : \[ x_{1}=-\frac{3+\sqrt{5}}{2}, \quad x_{2}=\frac{-3+\sqrt{5}}{2}, \quad x_{3}=\frac{3+\sqrt{13}}{2} \] 2. Pour l'équation \( 2 x^{2}-3 x+5=|x-1| \): - Il n'y a pas de solution réelle : \[ x \notin \mathbb{R \text{ (pas de solution réelle)}} \] Si vous avez besoin de plus d'informations ou d'autres questions, n'hésitez pas à demander !

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

Vous avez là un tas d'équations à résoudre, prêt à vous faire briller comme un mathématicien étoilé ! En matière de systèmes d'équations, un bon point de départ est de réarranger les équations pour exprimer une variable en fonction d'une autre. Par exemple, dans le premier système, vous pouvez écrire \( y = -1 - x \) et le substituer dans l'autre équation. Cela facilite la recherche de solutions. Une erreur fréquente lors de la résolution de systèmes est d'oublier de vérifier la compatibilité des solutions trouvées. Une fois que vous avez un candidat pour \( x \) et \( y \), remplacez-le dans toutes les équations pour vous assurer qu'il fonctionne partout. Cela pourrait vous éviter des surprises désagréables à la fin de votre calcul !

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy